Ijtihad Muhammadiyah dan Relevansinya Menyikapi Problem Kontemporer di Kota Ambon - Yusup Laisouw; Aholiab Watloly; La Jamaa; Simon Pieter Soegijono (Program Pascasarjana UKIM, 2024)
This research aims to find out and analyze the theoretical and relevance of Muhammadiyah ijtihad in responding to contemporary problems in Ambon City. This research uses a descriptive method with a qualitative approach. The descriptive method is based on approaches or book sources that are already known. Meanwhile, qualitative approach research is a way to answer research problems by assembling the data obtained. The research results show that Muhammadiyah's Ijtihad in responding to contemporary problems in Ambon City is not discriminatory. Muhammadiyah's Ijtihad in responding to modern problems (gender, feminism, and pluralism) in Ambon City does not conflict with the Qur’an and al-Hadith. Muhammadiyah's Ijtihad decision in Ambon City still refers to the Ijtihad decision of Muhammadiyah Central Leadership.